82.0k views
2 votes
What is the vertex of the graph of this function

y= -(x-1)(x+3)​

User Vhadalgi
by
5.0k points

1 Answer

6 votes

Answer:

Vertex = (-1,4).

Explanation:

Given equation is
y=-(x-1)(x+3).

Now we need to find the vertex of the graph of given function
y=-(x-1)(x+3).

To find that we can rewrite given function into vertex form


y=-(x-1)(x+3)


y=-(x^2+3x-1x-3)


y=-(x^2+2x-3)


y=-(x^2+2x+1-1-3)


y=-((x+1)^2-1-3)


y=-((x+1)^2-4)


y=-(x+1)^2+4

Now compar this equation with
y=a(x-h)^2+k

we get: h=-1, k=4

Hence vertex is (h,k) or (-1,4).

User Rick Gladwin
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.